Method Validation and Estimation of Measurement Uncertainty in the Determination of Total Polyphenols Content in Land Spinach by UV-Vis Spectrophotometry - Kuntari; Hasby S. Pandhyta (Jurnal Akademika Kimia, 2022)
Land spinach contains polyphenols which can be determined by the spectrophotometry method. Data on method validation and estimation of uncertainty measurement of polyphenols in land spinach are not yet available, so method validation and estimation of uncertainty measurement of polyphenol content determination were carried out using a UV-Vis spectrophotometer. The validation parameters of the tested methods include linearity, precision, accuracy, and LOD and LOQ. Analysis of total polyphenol content was carried out using the Folin-Ciocalteu method with the gallic acid standard. Based on the results of method validation, the equation of the line y = 0.7213x-0.0096 with a coefficient of determination (R2) is 0.9994. These results indicate that the correlation between standard concentrations of gallic acid and absorbance shows good linearity. Repeated measurements showed the average total polyphenol content and the estimated measurement uncertainty value was (3.0501±0,2886) mg/Kg GAE. The RSD percentage was obtained at 1.79% were the result entered the acceptance condition because it was ≤ 2%. Percent recovery was obtained at 81.50% and 85.66%, and the terms of acceptance range between 80-110%. The LOD and LOQ values obtained were 0.1024 mg/L and 0.3412 mg/L. Based on the data obtained, it can be said that the method used has good validity.